(untitled) (Environment & Health, 2018)
Objective: We analyzed modern environmental and hygienic risks of light industry in Ukraine and determined the ways for minimization of the pressure of the industrial enterprises on the environment. Materials and methods: Domestic and foreign scientific publications, statistical data. Results: The most topical ecological-and-hygienic problems of light industry were analyzed. The main pollutants of the production of different sub-sectors of light industry (textile, leather and fur, footwear, knitwear, clothing industry), their volumes, and the harmful effects on the environment were identified. The aggravation of the environmental problems was proved to dictate the need of the balance between the economical efficiency in the production activities of enterprises and environmental safety. Formation of the ecological safety of raw materials, materials and products requires the use of ecologically oriented technologies for wastewater treatment, emissions, reduction of the industrial waste generation and their negative influence on the environmental contamination.